Comparing Mining and Palm Oil Plantation Impacts on the Human Security of Local Communities - Suyani Indriastuti (Indonesian Journal of Geography, 2022)
Coal mining and palm oil plantations are important sectors for supporting development in Indonesia. However, these sectors are criticized as the cause of horizontal conflicts, deforestation, and natural disasters that threaten the human security of local communities. This paper aims to compare the extent to which coal mining industries and palm oil plantations have impacted the human security of local communities. For this purpose, this study applies comparative process tracing in the case of Kalimantan Timur and Kalimantan Tengah. This research found that palm oil plantations have lower negative impacts on the human security of local communities than coal mining industries. Mining has co-opted the livelihood of local communities. Local communities, most of whom initially work as farmers, lose job opportunities due to the transfer of agriculture to mining, which does not fit with the agency of local communities. In contrast, palm oil plantations establish cooperation with local laborers and local farmers in the Nucleus Estate Smallholder scheme (NES) which prevents unemployment. Therefore, in the context of local communities’ human security, it is better for government to develop palm oil plantations than coal mining.